Pembuatan Alat Uji Prestasi Mesin Motor Bakar Bensin Yamaha Lexam 155cc - Miftachul Ainza; Ardhika Noer M; Lidya Carolina B; Arga Adiputra (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Gasoline fuel motors are a type of motor that is widely used because they have advantages such as a relatively small weight ratio and engine power, the vibrations obtained are not large and are able to produce high performance. With the increasing gasoline engine technology, new innovations will emerge, always following the needs and tastes of various people. An internal combustion engine is a machine that converts chemical energy into mechanical energy. Tests are carried out to determine the performance of the machine through testing in the energy conversion laboratory. To understand the variables that affect performance in the manufacture of this test tool to be made for additional laboratory tests. With test data of 4000rpm, 5000rpm, 6000rpm, 7000rpm and 8000rpm rotation and load variations starting from 3,5,7,9 and 12kg. From the analysis of fuel consumption and its effect on engine power, it can be stated that with a rotation of 4000rpm torque = 2.94(Nm), effective power = 4431.16(kN.m/hour), average effective pressure = 0.019 (kpa), fuel consumption = 0.55 (kg/hour), specific fuel consumption = 0.00012 (kg/kN.m), fuel to air ratio = 0.00009 (m3/s), air mass flow rate = 0.013 (m3/s), volumetric efficiency = 2980.9% and thermal efficiency = 18.8% the greater the engine speed used, the higher the level of fuel consumed, as well as the effective power of the engine.